Data on genetic polymorphism of flax (Linum usitatissimum L.) pathogenic fungi of Fusarium, Colletotrichum, Aureobasidium, Septoria, and Melampsora genera - Roman O. Novakovskiy; Ekaterina M. Dvorianinova; Tatiana A. Rozhmina; Ludmila P. Kudryavtseva; Aleksey A. Gryzunov; Elena N. Pushkova; Liubov V. Povkhova; Anastasiya V. Snezhkina; George S. Krasnov; Anna V. Kudryavtseva; Nataliya V. Melnikova; Alexey A. Dmitriev (Data in Brief, 2020)
Being a valuable agricultural plant, flax (Linum usitatissimum L.) is used for oil and fiber production. However, the cultivation of this agriculture faces an urgent problem of flax susceptibility to fungal diseases. The most destructive ones are caused by the representatives of Fusarium, Colletotrichum, Aureobasidium, Septoria, and Melampsora genera, reducing flax yields significantly. To combat such pathogens effectively, it is of high importance to assess their genetic diversity that can be used to develop molecular markers to distinguish fungal genera and species. Morphological analysis traditionally carried out for fungal identification requires a given amount of time and tends to be difficult. In the present work, we determined the DNA sequences that are frequently used for phylogenetic studies in fungi – internal transcribed spacer (ITS) and beta-tubulin (tub2), translation elongation factor 1-alpha (tef1), RNA polymerase II largest subunit (RPB1), RNA polymerase II second largest subunit (RPB2), and minichromosome maintenance protein (MCM7) genes – for 203 flax fungal pathogens of Fusarium oxysporum, F. avenaceum, F. solani, F. sporotrichiella, F. moniliforme, F. culmorum, F. semitectum, F. gibbosum, Colletotrichum lini, Aureobasidium pullulans, Septoria linicola, and Melampsora lini species. The sequencing was performed using the Illumina MiSeq platform with a 300+300 bp kit, and on average, about 2350 reads per sample were obtained that allows accurate identification of the genetic polymorphism. Raw data are stored at the Sequence Read Archive under the accession number PRJNA596387. The obtained data can be used for fungal phylogenetic studies and the development of a PCR-based test system for flax pathogen identification.